THD MINIMIZATION OF VEHICLE-TO-GRID (V2G) IN FUEL CELL EVs WITH A DEVELOPED ELLIPTIC IIR FILTER - Bayrak, Gökay; Yılmaz, Alper (International Association for Hydrogen Energy, IAHE, 2022)
The popularity of fuel cell electric vehicles (FCEVs) and plug-in electric vehicles (PEVs) is a key factor in addressing the electricity demand. With vehicle-to-grid (V2G) applications, these vehicles can act as distributed generators. Total harmonic distortion (THD) in the connection of electric vehicle charge stations (EVCSs) capable with V2G technology with the grid should be fulfilling the values specified by international electrical standards. Although V2G topologies are improved, the use of a suitable filter is necessary to improve the power quality (PQ) of the system. Since analog filters bring additional losses to power losses caused by inverter and converter, software-based digital filters are also needed. Due to the implementation of the infinite impulse response (IIR) filter includes fewer parameters, it requires less memory and has less computational complexity. In this study, a low-pass elliptical IIR filter design is realized in real-time with the converter using LabVIEW infrastructure. When imbalances occur in the grid voltage, reducing bandwidth using phase locked loop (PLL) will not be enough to keep the system stable. This problem solved by adding a proposed low-pass elliptical IIR filter to the system.The results obtained by using the filter are presented in the paper and the THD value was obtained as 0.82% for converter capable V2G. © 2022 Proceedings of WHEC 2022 - 23rd World Hydrogen Energy Conference: Bridging Continents by H2. All rights reserved.
23rd World Hydrogen Energy Conference: Bridging Continents by H2, WHEC 2022 -- 2022-06-26 through 2022-06-30 -- Istanbul -- 186176
Keywords: Fuel cell electric vehicles (FCEVs); IIR filter design; Power quality; THD minimization; Vehicle-to-grid (V2G)